The effects of cochlear implantation in Japanese single-sided deafness patients: five case reports. (3rd May 2016) - Kitoh, Ryosuke; Moteki, Hideaki; Nishio, Shinya; Shinden, Seiichi; Kanzaki, Sho; Iwasaki, Satoshi; Ogawa, Kaoru; Usami, Shin-ichi
Abstract: Conclusion Cochlear implantation (CI) for Japanese single-sided deafness patients resulted in improved speech perception, increased sound localization accuracy, and reduced tinnitus handicap.Objectives This study reports results for five adult SSD cases with CI, focusing on the benefits they obtained in terms of speech recognition, sound localization, and tinnitus handicap.Methods Five Japanese patients meeting the eligibility criteria were included in this study. All patients were implanted with a fully inserted MED-EL Concerto FLEX28® implant (MED-EL, Innsbruck, Austria). Speech perception outcomes in noise, as well as sound localization and tinnitus disturbance, were assessed pre-surgically and at 1, 3, 6, and 12 months after CI activation.Results The Japanese monosyllable test score in noise improved gradually after implantation. In some cases, speech perception ability appeared unstable, particularly in the first 1–6 months after implantation. The sound localization ability showed marked improvement in all cases, with the disturbance to daily life caused by tinnitus also decreasing in all cases from the early post-operative period.